IJERPH (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Next year (2018), we will be celebrating the 15th anniversary of the International Journal of Environmental Research and Public Health—IJERPH (ISSN 1660-4601). Hence, we are currently organizing a Special Issue to commemorate this important milestone. Founded in 2004, IJERPH has experienced a tremendous growth in terms of the number and quality of scientific publications. With a 2016 impact factor of 2.101, IJERPH now ranks among the top international journals in the emerging field of environmental research and public health. As described on our website (https://www.mdpi.com/journal/ijerph), IJERPH is a peer-reviewed journal that focuses on the publication of scientific and technical information on the impacts of natural phenomena and anthropogenic factors on the quality of our environment, the interrelationships between environmental health and the quality of life, as well as the socio-cultural, political, economic, and legal considerations related to environmental stewardship and public health. Its primary areas of research interests include: Gene-environment interactions Environmental genomics and proteomics Environmental toxicology, mutagenesis and carcinogenesis Environmental epidemiology and disease control Health risk assessment and management Ecotoxicology, and ecological risk assessment and management Natural resources damage assessment Environmental chemistry and computational modeling Environmental policy and management Environmental engineering and biotechnology Emerging issues in environmental health and diseases Environmental education and public health To help celebrate the 15th anniversary, you are kindly invited to submit original articles, critical reviews, research notes, and short communications on any of the above-listed topics. Please also encourage any of our colleagues who may be interested to submit manuscripts. We expect that this issue will attract considerable attention, as we prepare to celebrate the excellent scientific contributions and socio-economic impacts of IJERPH over the past 15 years.